ANALISIS PEMBENTUKAN KARAKTER KREATIF SISWA MELALUI PEMBELAJARAN SENI RUPA DI SDN 2 PURWOSARI - Rachma Agustin, Della; Baedowi, Sunan; Arisyanto, Prasena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background that prompted this research was the low self confidence and lack of creativity of students in creating works of art in fine arts learning at SDN 2 Purwosari. Creative character is an important aspect in fine arts learning in elementary schools. However, in reality, students still rely on examples and detailed technical directions. This research focuses on 1) How fine arts activities are implemented; 2) How students' creative character is formed; 3) Supporting and inhibiting factors for the formation of creative character through fine arts learning at SDN 2 Purwosari. This research used a descriptive qualitative method with a naturalistic approach to gain an in-depth understanding of the learning phenomena taking place in the classroom. The subjects were teachers and students in grades I, III, and V of SDN 2 Purwosari. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. Data validity was tested through source and technique triangulation. The results of the study indicate that fine arts activities were implemented through practical activities tailored to the characteristics of students at each grade level. The process of developing creative character is demonstrated through students' abilities to develop ideas, choose shapes and colors, collaborate, try new techniques, refine their work, and solve problems during the work. Supporting factors include the teacher's role as a facilitator, creative freedom, the use of readily available media, collaboration among students, and student enthusiasm. While inhibiting factors include limited learning time, differences in student abilities, lack of self confidence, limited tools and materials, and technical difficulties in creating works. Based on the results of the study, it can be concluded that fine arts activities play a role in shaping students' creative character through creative experiences that provide opportunities for exploration and development of creativity. Based on these findings, the recommendation is that teachers continue to provide opportunities for students to develop ideas and creativity independently through a variety of fine arts activities.